2015
DOI: 10.1002/prca.201500002
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, biomarkers, and HIV‐1: A current perspective

Abstract: Despite more than three decades of extensive research, HIV-1 infection although well controlled with cART, remains incurable. Multifactorial complexity of the viral life cycle poses great challenges in understanding molecular mechanisms underlying this infection and the development of biomarkers, which we hope will lead us to its eradication. For a more in-depth understanding of how the virus interacts with host target cells, T cells and macrophages, proteomic profiling techniques that offer strategies to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…However, lack of detection of Tat in exosomes from the infected cells in these two studies cannot simply be interpreted as absence of the protein. LC-MS/MS has not been detected Tat protein in HIV-producing CD4 T cells (Li 2015; Santos et al 2012; Saphire et al 2006) and in sera of HIV-infected patients (Donnelly and Ciborowski 2016). Only one study has detected Tat protein in purified HIV using LC-MS/MS in combination with micro-capillary reversed-phase liquid chromatography (µRPLC) (Chertova et al 2006), which has been shown to improve detection of low-abundant proteins such as Tat (Tomlinson and Chicz 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of detection of Tat in exosomes from the infected cells in these two studies cannot simply be interpreted as absence of the protein. LC-MS/MS has not been detected Tat protein in HIV-producing CD4 T cells (Li 2015; Santos et al 2012; Saphire et al 2006) and in sera of HIV-infected patients (Donnelly and Ciborowski 2016). Only one study has detected Tat protein in purified HIV using LC-MS/MS in combination with micro-capillary reversed-phase liquid chromatography (µRPLC) (Chertova et al 2006), which has been shown to improve detection of low-abundant proteins such as Tat (Tomlinson and Chicz 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Every step brings with it some degree of variability. [ 14 ] Sample preparation, instrumentation, targeted versus global approaches, and data analysis are a few of the factors that influence results, and thus the conclusions are drawn and knowledge gained. These issues can make it difficult to compare study results and to build a clearer picture of HIV infection in macrophages, and ultimately, of HIV infection in humans overall.…”
Section: Quantitative Proteomics: Experimental Design To Maximize Thementioning
confidence: 99%
“…For a more comprehensive discussion of viral proteins, we refer readers to our previous review. [ 14 ]…”
Section: Viral Proteinsmentioning
confidence: 99%
“…Some proteomic studies have also been performed, but they were not very reproducible, as indicated in a recent review by Donnelly and Ciborowski (2016). To our knowledge, few epigenomic studies have been published to date in HIV/AIDS.…”
Section: Proteomic and Epigenomic Studiesmentioning
confidence: 99%